PENERAPAN AWARENESS TRAINING UNTUK PENINGKATAN PSYCHOLOGICAL WELL-BEING PADA KOMUNITAS SATRIA NUSANTARA SURABAYA - Miftakhul Jannah; Riza Noviana Khoirunnisa; Satiningsih Satiningsih; Yohana Wuri Satwika; Navylia Tirta Kencana; Reza Asep Adi Purnomo (Yayasan Education and Social Center, 2023)
The Satria Nusantara (SN) Respiratory Arts Institute (LSP) is a martial arts college that develops the six human senses, where this institution was created as a form of defense of various traditional cultural values through pencak silat in order to achieve the goal of improving health and fitness as a form of physical endurance. and health promotion through exercise. However, apart from being physically healthy, mental health is also important. Psychological well-being is a healthy psychological condition, free from mental problems and functioning optimally. This is the background for the service team to provide training in the form of awareness training which aims to increase understanding of oneself and the behavior of others. This activity was held at LSP Satria Nusantara in Surabaya using lecture and direct practice methods. Participants in this training are all members of LSP Satria Nusantara. This activity lasted for 2 months. Through this activity, it is hoped that members of LSP Satria Nusantara Surabaya will be helped in their personal and social development